Draft Third Five Year Plan 1961-66 (Volume VII) Housing Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1961)
Housing facilities for workers employed in public sector also need to be expanded. In developing private constructions, Low Income Group Housing Scheme is in operation and will be continued. Non-availability of developed plots is impeding the progress of this scheme. the difficulty is proposed to be overcome by availing of the financial assistance in accordance with para 4 of the Low Income Group Housing Scheme for developing plots around Port Blair for sale to prospective builders on a no-profit-no-loss basis. Accommodation is also required for locating new offices in the various parts of the territory.
Andaman and Nicobar Administration